Thermally induced metallurgical transformations in WC-17Co thermal spray coatings as a function of carbide dissolution: Part 2 - Heat-treated coatings. (April 2021) - Matthews, S.; Ansbro, J.; Berndt, C.C.; Ang, A.S.M.
Abstract: Tungsten carbide‑cobalt (WC-Co) thermal spray coatings are widely used for ambient temperature wear applications but are typically generated from feedstocks with 1–5 μm carbide particles rather than more desirable <1 μm carbide particles, due to challenges of carbide dissolution and carbon loss in-flight. This work explores a novel processing route for the WC-Co system that has been conceptually proven for the Cr3 C2 -NiCr system. The tendency for carbides to dissolve in-flight is maximised in this approach, with subsequent heat treatment used to precipitate submicron carbide particles. Part 1 of this two-part series assessed the theoretical feasibility of applying this concept to the Co-W-C system for WC-17wt%Co composites, and characterised high velocity oxygen fuel (HVOF), plasma Ar-He and plasma Ar-H2 coatings. In this follow-up paper, the powder and coating samples were characterised by Differential Scanning Calorimetry (DSC), followed by heat treatments below and above the identified phase transition temperatures. Compositional and microstructural analysis led to identification of the reactions accounting for each of the DSC peaks. These observations were contrasted with theoretical predictions as a function of the extent of carbide dissolution/decomposition and carbon loss in the as-sprayed coatings. Highlights: Characterised phase transition temperatures in WC-17wt%Co thermal spray coatings First DSC peak: transformation of the amorphous binder to WC, metallic Co and Co3 W3 C Second peak: transformation of the metastable Co3 W3 C to the equilibrium Co6 W6 C phase Plasma coatings: an additional transformation of WC1-X to form W2 C and WC occurred